Glutathione s-transferase: an overview on distribution of GSTM1 and GSTT1 polymorphisms in Malaysian and other populations - Wan Rashidi, Wan Nooremira; Abu Bakar @ Jamaludin, Suhaili (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Glutathione s-transferases (GSTs) are the vital enzymes involved in Phase II metabolism to detoxify a wide range of carcinogenic metabolites in the body. GST class mu-1 (GSTM1) and GST class theta-1 (GSTT1) are the genes encoding for the GST isoenzymes. Nevertheless, both genes were frequently reported absent (null) in most of the populations at different frequencies. Null polymorphism will affect the production of GSTs and impair the ability to eliminate carcinogenic compounds which had been shown to expose null individuals to high risk of several cancers such as gastric and lung cancer. Thus, this review will briefly summarize on the GSTM1 and GSTT1 polymorphisms, frequencies of null variants in populations worldwide, including Malaysian, and their relevancy to the underlying basis of toxicological response to xenobiotics. Additionally, the genotyping assays used in GST studies will also be discussed.